2003
DOI: 10.1126/science.1087441
|View full text |Cite
|
Sign up to set email alerts
|

A Dearth of Dark Matter in Ordinary Elliptical Galaxies

Abstract: The kinematics of the outer parts of three intermediate-luminosity elliptical galaxies have been studied using the Planetary Nebula Spectrograph. The galaxies' velocity dispersion profiles are found to decline with radius; dynamical modeling of the data indicates the presence of little if any dark matter in these galaxies' halos. This surprising result conflicts with findings in other galaxy types, and poses a challenge to current galaxy formation theories.Over the past twenty-five years, astronomers have gone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
531
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(578 citation statements)
references
References 33 publications
(31 reference statements)
36
531
11
Order By: Relevance
“…Although they have been detected around early-type galaxies for over a decade (e.g. Saglia, Bertin & Stiavelli 1992;Franx, van Gorkom & de Zeeuw 1994), there have been claims that they are not always required (Romanowsky et al 2003).…”
Section: Motivationsmentioning
confidence: 99%
“…Although they have been detected around early-type galaxies for over a decade (e.g. Saglia, Bertin & Stiavelli 1992;Franx, van Gorkom & de Zeeuw 1994), there have been claims that they are not always required (Romanowsky et al 2003).…”
Section: Motivationsmentioning
confidence: 99%
“…Studies by Ciardullo et al (1993); Méndez et al (2001Méndez et al ( , 2009Romanowsky et al (2003) indicated that the kinematic profile of intermediate luminosity ellipticals are consistent with no dark matter, or much less that what predicted by the ΛCDM model. The different teams adopted different modeling techniques, including isotropic or constant anisotropic Jeans models fitting several moments of the PNe velocity distribution, which lead to results consistent to each others.…”
Section: Mass Distribution In Early-type Galaxies: "Lost and Found" Dmentioning
confidence: 99%
“…Since the work of Arnaboldi et al (1994) on NGC 1399 and of Hui et al (1995) on Centaurus A (NGC 5128), there has been a considerable success in mapping the kinematics of the stellar population in the outer regions of ETGs out to 5R e (Arnaboldi et al 1996;Arnaboldi et al 1998;Méndez et al 2001;Romanowsky et al 2003;Coccato et al 2009;Napolitano et al 2009;McNeil et al 2010;Napolitano et al 2011;Teodorescu et al 2011;Cortesi et al 2011), and intracluster light (ICL) in nearby clusters (Arnaboldi et al 2004;Gerhard et al 2005;Gerhard et al 2007;Doherty et al 2009;Ventimiglia et al 2011).…”
Section: Planetary Nebulae As Kinematical Tracersmentioning
confidence: 99%